MENGOPTIMALKAN PENGELOLAAN SARANA DAN PRASARANA KANTOR DI SMP SWASTA PENRAUJAN KEC. SUNGGAL KAB. DELI SERDANG - H. Tengku Darmansah; Audia Amanda Br Tarigan; Nur Aini; Zulfikar Lubis (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Management of office facilities and infrastructure is very important because it can affect employee performance at work, both in working time and comfort in doing work. With adequate office facilities and infrastructure, employee performance will increase so that they can work better and achieve optimal work results. Penraujan Private Middle School in Sunggal District, Deli Serdang Regency, which is one of the junior high schools in Sunggal Kanan, has adequate office facilities. Research on "Optimizing the Management of Office Facilities and Infrastructure in Middle Schools, Sunggal District, Deli Serdang Regency" is the aim of this research. This type of research is a field study using qualitative methods. The research results show that the management of facilities and infrastructure is a complex process that includes planning, organizing and monitoring by an organization. Implementing the management of office facilities and infrastructure (sarpras) is a process that involves various steps, from planning to supervision. Some obstacles in managing office facilities and infrastructure are excessive pressure on facilities and a lack of understanding of what needs to be done.